Sequence and Genomic Analysis of a Rhesus Macaque Rhadinovirus with Similarity to Kaposi’s Sarcoma-Associated Herpesvirus/Human Herpesvirus 8 - Searles, Robert P. (American Society for Microbiology, 1999)
We have sequenced the long unique region (LUR) and characterized the terminal repeats of the genome of a rhesus rhadinovirus (RRV), strain 17577. The LUR as sequenced is 131,364 bp in length, with a G+C content of 52.2% and a CpG ratio of 1.11. The genome codes for 79 open reading frames (ORFs), with 67 of these ORFs similar to genes found in both Kaposi’s sarcoma-associated herpesvirus (KSHV) (formal name, human herpesvirus 8) and herpesvirus saimiri. Eight of the 12 unique genes show similarity to genes found in KSHV, including genes for viral interleukin-6, viral macrophage inflammatory protein, and a family of viral interferon regulatory factors (vIRFs). Genomic organization is essentially colinear with KSHV, the primary differences being the number of cytokine and IRF genes and the location of the gene for dihydrofolate reductase. Highly repetitive sequences are located in positions corresponding to repetitive sequences found in KSHV. Phylogenetic analysis of several ORFs supports the similarity between RRV and KSHV. Overall, the sequence, structural, and phylogenetic data combine to provide strong evidence that RRV 17577 is the rhesus macaque homolog of KSHV.